COMPARATIVE STUDY BETWEEN CIRC AND CONTENT BASED INSTRUCTION IN TEACHING READING - Fatimah, Ari Putri (Universitas Pendidikan Mandalika, 2016)
This study is aimed at finding out the different influence between two methods that is CIRC and CBI in teaching reading and to find out is there any influence between CIRC and CBI in teaching reading. Using CIRC was had positive effect to students score in learning reading and using CBI was had no effect to students score in learning reading. The kind of this study is causal experimental research. The population of this study was all the students of the second grade students at SMP Negeri 6 Woja Dompu that consist of 100 students from four classes. In which the sample of this research used two classes where each group consist of 25 students. Significant of the sample were divided into two group which were experimental group and control group. The experimental was taught by CIRC and control taught by CBI. The instruments that used the data were objective test with multiple choice were analyzed by using t-test formula. CIRC class get total score of pre-test is 1055 and pos-test score is 1605 and in CBI class get total score of pre-test is 1245 and pos-test score is 1540. The result of the analysis, it showed that the value of ttest(t obtained) is 1,890 was higher than ttableis 1,677. Based on the result of this investigation, it was proved that the null hypothesis (Ho) was clearly rejected. Therefore the alternative hypothesis is accepted.